Do Workload, Self-Efficacy, and Self-Esteem Affect Banking Employee Performance? - Didik Arif Raihan; Claudia, Meiske; R.R. Yulianti Prihatiningrum (HM Publisher, 2024)
A workload is one of the factors that affect employee performance. A workload is a set or number of activities an organizational unit must complete within the specified time. The high workload in the form of tasks and responsibilities given to employees will lead to less than optimal work results. The addition of workload will undoubtedly affect the psychological state of the employee itself. These psychological disorders will certainly have an impact on the performance shown. This research aims to test and analyze the effect of workload, self-efficacy, and self-esteem on banking employee performance. This type of research is included in explanatory research. The population is 63 customer service employees and tellers of Bank X in Banjarmasin. The sampling method uses a population sampling technique (saturated sample) and uses multiple linear regression for data analysis. The research results show that workload, self-efficacy, and self-esteem significantly affect employee performance. In conclusion, not only workload and self-efficacy but also self-esteem, significantly affect employee performance.